KEANEKARAGAMAN KUPU-KUPU DI KECAMATAN SUKARAME KOTA PALEMBANG PROVINSI SUMATERA SELATAN - Ririn Eka Putri (Universitas PGRI Palembang, 2014)
The research about diversity of buterflys at Sukarame village was conducted March - April 2015. The objective of this research was collect buterflys. This research utilited the direct observation method during three week. This method used insecting nets. The result of the identification geted 7 Order, 3 Family, 7 Genera, dan 10 Spesies. Key words : diversity, buterfly, Sukarame